1991
DOI: 10.1055/s-2008-1042484
|View full text |Cite
|
Sign up to set email alerts
|

SD-Mice - An Animal Model for Complex Anorectal Malformations*

Abstract: Animal models for morphological investigations of anorectal malformations are barely known to pediatric surgeons. In this study the morphological characteristics of a spontaneous mutation of the house mouse, the so-called SD-mouse, are described. The semidominant gene SD exerts its influence on the anorectum, the urogenital system and the axial skeleton. Many heterozygous (SD/+) and all homozygous (SD/SD) animals die shortly after birth due to their malformations. Surviving heterozygotes, identified by their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…18 More recently, studies of Sd mice noted that the most consistent finding in this animal model was the loss of the dorsal cloaca and the presence of a short cloacal membrane. 16,56 In our anorectal mouse models, we found no evidence of active septation or lateral ridges formation/fusion on transverse sections of our mutant embryos, and similar to the Sd mice, we also observed a lack of formation of a normal dorsal cloaca. Our data now introduces a developmental model that furthers our understanding of anorectal malformation beyond the previous anatomical-based theories.…”
Section: Gli2mentioning
confidence: 66%
“…18 More recently, studies of Sd mice noted that the most consistent finding in this animal model was the loss of the dorsal cloaca and the presence of a short cloacal membrane. 16,56 In our anorectal mouse models, we found no evidence of active septation or lateral ridges formation/fusion on transverse sections of our mutant embryos, and similar to the Sd mice, we also observed a lack of formation of a normal dorsal cloaca. Our data now introduces a developmental model that furthers our understanding of anorectal malformation beyond the previous anatomical-based theories.…”
Section: Gli2mentioning
confidence: 66%
“…These mice have an autosomal-dominant trait for imperforate anus and pass on this semi-dominant trait with high penetrance, where all of the homozygotes and most of the heterozygotes are affected. Kluth et al [83] looked at the spectrum of anorectal anomalies in this model and found that the pathological anatomical malformations in the heterozygous Sd mouse group were very similar to those seen in human neonates with anorectal anomalies as well as previous porcine models, which have been described. To date, the gene defective in Sd mice has yet to be identified.…”
Section: Surgical Models Of Ea and Tefmentioning
confidence: 69%
“…Several animal models for ARM are known. For example, Danforth's short tail (Sd) mouse is one of the oldest animal models for ARM [5]. The incidence of ARM is 36% in Sd/+ and 100% in Sd/Sd mice.…”
Section: Discussionmentioning
confidence: 99%